NCD in Marginalised Population - Abdullah Zawawi, Zaitul Akmal; binti Che Ya, Siti Nuryati; Waqar, Salman; Samsudin, Shahrizal Azwan (International Journal of Human and Health Sciences (IJHHS), 2024)
Non-communicable diseases (NCDs) have emerged as a significant health concern worldwide, and indigenous populations in Malaysia are not immune to this health burden. The indigenous population in Malaysia comprises diverse ethnic groups such as Kadazan, Penan, Dayak, among others. Orang Asli is one of the indigenous populations in Peninsular Malaysia that can be divided into ‘pinggiran’ and ‘pedalaman’ based on their locality. Over the past few decades, their traditional lifestyles and dietary habits have undergone significant changes due to urbanization and modernization. These changes have led to an epidemiological transition, resulting in an increased prevalence of NCDs among Orang Asli communities. These NCDs pose considerable health threats and challenges impacting the overall wellbeing of this population. Various factors contribute to the high burden of NCDs among Orang Asli people in Malaysia. Socioeconomic disparities, limited access to healthcare services, language-cultural barriers, and lacking health awareness programs are some of the key challenges hindering effective NCD prevention and management. Interestingly, we are facing different health challenges in handling this population with food insecurity among Orang Asli ‘pedalaman’ vs urbanization of Orang Asli ‘pinggiran’. A comprehensive and culturally sensitive approach is required to address the issue of NCD among this marginalized population. Collaborative efforts between government agencies, non-governmental organizations, and local community leaders are essential to implement sustainable and effective strategies. A holistic approach that addresses the social determinants of health and integrates indigenous knowledge with evidence-based practices is crucial to improve health outcomes and reduce the burden of NCDs of the Orang Asli community. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S22